My place - Morgan, Sally, 1951 January 18- (Freemantle : Freemantle Arts Centre Press, 1999)
Sally Morgan traces her life growing up in suburban Perth in the 1950s and 1960s. Through her memories, hidden knowledge about her Aboriginal past is uncovered, and three generations of her family are gradually drawn into a search for truth.
Autobiography.
Keywords: Morgan, Sally, -- 1951 January 18-; Aboriginal Australians -- Biography; Women, Aboriginal Australian -- Biography; Aboriginal Australians -- Social life and customs